Analisis Critical Success Factors (CSF) Green Finance dalam Pengembangan Infrastruktur Smart City di Indonesia - Davin Adriel Rawis (Universitas Batanghari Jambi, 2026)
This study aims to analyze the Critical Success Factors of green finance in the development of Smart City infrastructure in Indonesia. The research was conducted through data processing and analysis of six main variables, namely public literacy, macroeconomic conditions, environmentally friendly investment, operations, risk management, and regulation. The results indicate that, simultaneously, all variables have a significant effect on the impact of green finance implementation on Smart City development in Indonesia. Partially, macroeconomic conditions, environmentally friendly investment, and risk management have a significant influence on the impact of green finance implementation, while regulation, public literacy, and operational factors do not show a significant effect. Environmentally friendly investment is the most dominant factor, as indicated by the highest positive regression coefficient compared to other variables. These findings highlight that increasing environmentally friendly investment provides the greatest and most tangible contribution to the successful development of sustainable Smart City infrastructure in Indonesia.